2017
DOI: 10.1111/ijsw.12273
|View full text |Cite
|
Sign up to set email alerts
|

Risk and vulnerability in social assistance receipt of young adults in Finland

Abstract: Social background may affect not only individuals’ wellbeing, but also their ability to manage the typical and problematic transitions occurring during young adulthood. Hence, this article has used Finnish population register data to analyse how social background and critical life‐course factors predict the number of months of social assistance received annually among young adults aged 19–29. Special interest was given to asking whether those with a disadvantaged social background are more vulnerable to the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Driessen and Smit (2007) showed that there is a connection between immigrant parents' societal participation and cognitive outcome measures, such as the children's language and mathematics skills. It also seems that having only a basic education is more harmful for those have a disadvantaged social background (Ilmakunnas, 2018). Therefore, it is essential to determine adult asylum seekers' educational needs.…”
Section: Participantsmentioning
confidence: 99%
“…Driessen and Smit (2007) showed that there is a connection between immigrant parents' societal participation and cognitive outcome measures, such as the children's language and mathematics skills. It also seems that having only a basic education is more harmful for those have a disadvantaged social background (Ilmakunnas, 2018). Therefore, it is essential to determine adult asylum seekers' educational needs.…”
Section: Participantsmentioning
confidence: 99%
“…Bäckman and Bergmark () reviewed the findings of earlier research by stating that male sex, being a single adult, ethnic minority status, low educational achievement, substance abuse, low employability, and poor physical and mental health were found to be predictors of low social assistance exit rates. Some studies have concentrated especially on social assistance receipt among young adults (Ilmakunnas, ; Kauppinen et al, ; Lorentzen et al, ; Wiborg & Møberg, ). Moving out of the parental home has been shown to be a strong predictor of social assistance receipt in the Nordic countries (Kauppinen et al, ; Lorentzen et al, ).…”
Section: Life Course and Social Assistance Dynamicsmentioning
confidence: 99%
“…Young single parents are at risk of social assistance receipt (Lorentzen et al, ) and long‐term receipt in particular (Kauppinen et al, ). Among young adults, low education is an important predictor of social assistance receipt (Ilmakunnas, ; Lorentzen et al, ; Wiborg & Møberg, ). Earlier studies have also illustrated that disadvantaged social background is associated with social assistance receipt (Hyggen, ; Ilmakunnas, ; Kauppinen et al, ; Lorentzen et al, ; Wiborg & Møberg, ).…”
Section: Life Course and Social Assistance Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of childhood economic disadvantage on children's later wellbeing has been documented extensively over past decades (e.g., Hansen, 2008;Holzer, Schanzenbach, Duncan, & Ludwig, 2007;Ilmakunnas, 2018;Mayer, 1997;McLoyd, 1998;Saraceno, 2002). When comparing children from more affluent families to children living in low-income families, earlier studies have found that children growing up in poverty are more likely, for example, to have health, behavioural, and emotional problems; to drop out of school; to have low academic achievement; and a risk of an intergenerational cycle of welfare receipt (e.g.…”
Section: Introductionmentioning
confidence: 99%